Evaluación del crecimiento y rendimiento en el cultivo de maní (Arachis hypogaea L. var. INIAP-381), mediante aplicaciones de abonos orgánicos nutrisano y nutribiol en Zapotepamba, provincia de Loja - Ludeña Torres, Sila Pamela (2022)
This research work was carried out at the Binational Technical Training Center Zapotepamba, canton Avocados, Loja province, with the objective of evaluating the growth and yield of the crop, with different doses of organic fertilizers, as well as the profitability of each treatment. A Completely Randomized Design (CRD) with five treatments and four replications was used, with a total of 20 experimental units. The treatments were as follows: C (control); T1 (3 Tn/ha Nutrisano + 100 l/ha Nutribiol ); T2 (6 Tn/ha Nutrisano + 150 l/ha Nutribiol); T3 (9 Tn/ha Nutrisano + 200 l/ha Nutribiol) and T4 (12 Tn/ha Nutrisano + 250 l/ha Nutribiol); the variables to be evaluated consisted of peanut crop phenology (vegetative and reproductive), growth variables and yield parameters. For the statistical analysis of data, the Insfotat software was used using analysis of variance (ANOVA), to evaluate the statistical differences, the Tukey test at 95% was used, a Pearson correlation at 95% between the variables and the benefit-cost ratio was calculated. The treatments did not significantly affect the variables plant height, stem diameter, emergence, number of nodules, root length, aerial dry biomass, weight of 100 pods and seeds, number of pods/plant, length and equatorial diameter of pods. While biofertilization with T1 (3 Tn/ha Nutrisane + 100 l/ha Nutribiol) significantly influenced the number of branches (5), seed length (1.59 cm), as well as the highest yield with 2.8 Tn/ha, while the lowest yield was for T4 (12 Tn/ha Nutrisane + 250 l/ha Nutribiol) with 2. 66 Tn/ha; followed by T2 (6 Tn/ha Nutrisano + 150 l/ha Nutribiol) which influenced the number of seed/pod (4); continuing with T3 (9 Tn/ha Nutrisano + 200 l/ha Nutribiol) obtained the highest equatorial seed diameter (0.94 cm); and with T4 (12 Tn/ha Nutrisano + 250 l/ha Nutribiol) the root dry biomass (28.75 g). In relation to the benefit-cost analysis, with the control treatment (control) a value of 1.38 was obtained, resulting to be profitable, while in the other treatments values lower than 1 were obtained. Keyword: Arachis hypogaea, biofertilization, phenology, vegetative growth, yield.